KAJIAN DAMPAK EMISI UDARA TERHADAP LINGKUNGAN PADA PROSES PRODUKSI MINYAK DAN GAS BUMI DI PT. X MENGGUNAKAN METODE LIFE CYCLE ASSESSMENT (LCA) - Saraswati, Theresia Canthika; Assomadi, Abdu Fadli (Purifikasi, 2023)
PT. X has conducted a Life Cycle Assessment (LCA) study in 2019. However, it has not been proven that the air emission reduction program that has been implemented is effective in reducing the environmental impacts that occur. In this study, the LCA study is continued to identify the largest environmental impacts that occur and hotspot units after implementing the air emission reduction program and determine the effectiveness of the program. SimaPro software was used to conduct the LCA analysis, with a midpoint approach and using the CML-IA Baseline method. Based on the LCA analysis, the biggest environmental impacts that occur at PT X are acidification in SP A, B, C and global warming (GWP100a) in SP D. the air emission reduction program that has been implemented since 2019 has effectively reduced the impacts that occur. The recommended improvements to reduce the impact of acidification and global warming are replacing diesel engines with gas engines, installing Non-Selective Catalytic Reduction (NCSR), utilizing flare gas into compresses natural gas, and enhancing oil recovery using carbon capture separation technology to capture CO2 gas.